Solvent Influence Upon Complex Formation Between Dibenzo-18-Crown-6 and Cd2+, Cu2+, Tl+ and Zn2+ Cations in Dimethylsulfoxide-Methanol Binary Mixtures - HOSSEIN ROUNAGHI, GHOLAM; GAMIL GEREY, NOORANI (Asian Journal of Chemistry, 2010)
The complexation reactions between Cd2+, Cu2+, Tl+ and Zn2+ cations with dibenzo-18-crown-6 (DB18C6) were studied in DMSO-MeOH binary mixtures at different temperatures using conductometric method. In all cases, DB18C6 froms 1:1 complexes with Cd2+, Cu2+, Tl+ and Zn2+ cations. With the exception of Tl+ cation in pure methanol, addition of DB18C6 to the cations solutions causes a continous increase in the molar conductivity which indicates that the mobility of the complexed cations is more than the uncomplexed ones. The values of stability constants of the complexes which were determined from conductometric plots using the GENPLOT computer program, show that the stability of the complexes is affected by the nature and composition of the mixed solvents. A non-linear behaviour was observed between the log Kf and the composition of the mixed solvents for all of the complexes. The selectivity of DB18C6 for Cu2+, Cd2+, Tl+ and Zn2+ is sensitive to the solvent composition and in some cases the order of selectivity is reversed in certain compositions of the mixed solvent systems. The selectivity of DB18C6 for the cations in pure MeOH is : Tl+ > Cd2+ > Cu2+ > Zn2+. The values of thermodynamic parameters( ΔS°c , ΔH°c ) for formation of (DB18C6)Cd2+, (DB18C6)Cu2+, (DB18Cd)Tl+ and (DB18C6)Zn2+ complexes were obtained from temperature dependence of the formation constants of the complexes using the van't Hoff plots. The obtained results show that in most cases, the complexation reactions between DB18C6 and these heavy metal cations are enthalpy destabilized but entropy stabilized.